Kepemimpinan Profetik dan Nilai Kebangsaan: Strategi Mitigasi Krisis Kolaborasi dan Resistensi Organisasional di Madrasah - Ahmad Sukandar; Deding Ishak; Addin Mustofa Kamal; Resvitasari Resvitasari; Faridah Faridah (Universitas Indraprasta PGRI, 2026)
Madrasas, as Islamic educational institutions, face various internal challenges, particularly related to weak collaboration among members of the madrasa community, low participation in decision-making, and the emergence of resistance to leadership policies. These conditions are often influenced by leadership styles that do not fully integrate moral, spiritual, and national values ​​in a balanced manner. This study aims to position prophetic leadership based on prophetic values ​​as an ethical and practical framework for developing humanistic and transformative madrasa leadership. These values ​​are combined with national values, particularly religious moderation, in an effort to foster an inclusive, tolerant, and collaborative attitude in madrasa organizational management. This research uses a qualitative approach with a case study design, aiming to gain an in-depth understanding of the internal leadership dynamics in madrasas and efforts to mitigate the crisis of collaboration and organizational resistance. The results indicate that the crisis of collaboration and organizational resistance in madrasas can be minimized through the implementation of consistent, transparent, and participatory prophetic leadership, oriented toward the value of religious moderation. The integration of Islamic values ​​and nationalism has been proven to strengthen the trust of madrasa communities, improve internal communication, and build a harmonious work culture.